Value of colchicine as treatment for recurrent oral ulcers: A systematic review. (12th May 2020) - Cabras, Marco; Carrozzo, Marco; Gambino, Alessio; Broccoletti, Roberto; Sciascia, Savino; Baldovino, Simone; Arduino, Paolo Giacomo
Abstract: Background: In oral medicine, colchicine is a therapeutic alternative for idiopathic recurrent aphthous stomatitis (RAS), Behçet disease (BD), periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis (PFAPA) syndrome, and mouth and genitals ulcers with inflamed cartilage (MAGIC) syndrome. The present review aims to evaluate reliability of colchicine against recurrent oral ulcers. Methods: A systematic review was conducted, with the following PICO (Patient, Intervention, Control, Outcome) question: "In populations with idiopathic or secondary recurrent oral ulcers, is colchicine more effective in improving pain and accelerating healing, compared to other intervention or placebo?" Results: Seven RCTs and 3 OCTs were considered eligible. Four RCTs focused on BD, two RCTs and three OCTs on RAS, and one RCT on PFAPA syndrome. Heterogeneity between RCTs prevented from meta‐analysis. Regarding BD, no significant difference between colchicine and placebo was found in two of three placebo‐controlled RCTs, whereas the third RCT showed benefit. A comparative RCT found ciclosporin more effective than colchicine for oral lesions of BD. One open‐label RCT showed promising but partial results on colchicine in reducing PFAPA attacks, when compared to corticosteroids. Concerning RAS, colchicine appeared less effective than clofazimine, thalidomide and dapsone, and with outcomes similar to low‐dosage corticosteroids but higher gastric discomfort than prednisolone. One OCT reported positive results compared with no treatment but a RCT found no difference with placebo. Conclusion: Role of colchicine as treatment for idiopathic or secondary recurrent oral ulcers is still controversial. Further standardized RCTs and crossover trials are needed.